Metal-free synthesis of phosphinoylchroman-4-ones via a radical phosphinoylation–cyclization cascade mediated by K2S2O8 - Liu, Qiang; Lu, Weibang; Xie, Guanqun; Wang, Xiaoxia (Beilstein Journal of Organic Chemistry, 2020)
A variety of chroman-4-ones bearing phosphine oxide motifs were conveniently synthesized from readily available diphenylphosphine oxides and alkenyl aldehydes via a metal-free tandem phosphinoylation/cyclization protocol. The reaction utilizes K2S2O8 as oxidant and proceeds in DMSO/H2O at environmentally benign conditions with a broad substrate scope and afforded the title compounds in moderate yields.
Keywords: chroman-4-ones; diphenylphosphine oxide; metal-free; potassium persulfate; radical cyclization

(untitled) - Xiong, L.; Hu, H.; Wei, C.-W.; Yu, B. (Eur. J. Org. Chem., 2020)

(untitled) - Maiti, A.; Cuendet, M.; Croy, V. L.; Endringer, D. C.; Pezzuto, J. M.; Cushman, M. (J. Med. Chem., 2007)

(untitled) - Wang, H.-C.; Chang, F.-R.; Huang, T.-J.; Kuo, C.-Y.; Tsai, Y.-C.; Wu, C.-C. (Chem. Res. Toxicol., 2015)

(untitled) - Trost, B. M.; Gnanamani, E.; Kalnmals, C. A.; Hung, C.-I; Tracy, J. S. (J. Am. Chem. Soc., 2019)

(untitled) - Bagle, P. N.; Mane, M. V.; Sancheti, S. P.; Gade, A. B.; Shaikh, S. R.; Baik, M.-H.; Patil, N. T. (Org. Lett., 2019)

(untitled) - Hirano, K.; Biju, A. T.; Piel, I.; Glorius, F. (J. Am. Chem. Soc., 2009)

(untitled) - Biju, A. T.; Wurz, N. E.; Glorius, F. (J. Am. Chem. Soc., 2010)

(untitled) - Piel, I.; Steinmetz, M.; Hirano, K.; Fröhlich, R.; Grimme, S.; Glorius, F. (Angew. Chem., Int. Ed., 2011)

(untitled) - Yoshida, M.; Fujino, Y.; Doi, T. (Org. Lett., 2011)

(untitled) - Yoshida, M.; Saito, K.; Fujino, Y.; Doi, T. (Chem. Commun., 2012)

(untitled) - Zhang, L.; Dewan, V.; Yin, H. (J. Med. Chem., 2017)

(untitled) - Zhao, J.; Zhao, Y.; Fu, H. (Org. Lett., 2012)

(untitled) - Kim, H. Y.; Song, E.; Oh, K. (Org. Lett., 2017)

(untitled) - Zhao, X.; Zhou, J.; Lin, S.; Jin, X.; Liu, R. (Org. Lett., 2017)

(untitled) - He, X.-K.; Cai, B.-G.; Yang, Q.-Q.; Wang, L.; Xuan, J. (Chem. – Asian J., 2019)

(untitled) - Huang, H.-L.; Du, J.-Y.; Li, Q.-L.; Gao, F.; Ma, C.-L. (J. Org. Chem., 2020)

(untitled) - Hu, H.; Chen, X.; Sun, K.; Wang, J.; Liu, Y.; Liu, H.; Fan, L.; Yu, B.; Sun, Y.; Qu, L.; Zhao, Y. (Org. Lett., 2018)

(untitled) - Hu, H.; Chen, X.; Sun, K.; Wang, J.; Liu, Y.; Liu, H.; Yu, B.; Sun, Y.; Qu, L.; Zhao, Y. (Org. Chem. Front., 2018)

(untitled) - Liu, M.-C.; Liu, W.; Wu, H.-Y.; Zhou, Y.-B.; Ding, Q.; Peng, Y. (Org. Chem. Front., 2020)

(untitled) - Tang, L.; Yang, Z.; Chang, X.; Jiao, J.; Ma, X.; Rao, W.; Zhou, Q.; Zheng, L. (Org. Lett., 2018)

(untitled) - Chen, L.; Liu, X.-Y.; Zou, Y.-X. (Adv. Synth. Catal., 2020)

(untitled) - Chen, C.; Bao, Y.; Zhao, J.; Zhu, B. (Chem. Commun., 2019)

(untitled) - Gao, Y.; Tang, G.; Zhao, Y. (Phosphorus, Sulfur Silicon Relat. Elem., 2017)

(untitled) - Cai, B.-G.; Xuan, J.; Xiao, W.-J. (Sci. Bull., 2019)

(untitled) - Song, Y.; Wang, L.; Duan, Z.; Mathey, F. (Chin. Chem. Lett., 2020)

(untitled) - Liu, X.-C.; Chen, X.-L.; Liu, Y.; Sun, K.; Peng, Y.-Y.; Qu, L.-B.; Yu, B. (ChemSusChem, 2020)

(untitled) - Cullen, S. C.; Rovis, T. (Org. Lett., 2008)

(untitled) - Zhao, J.; Li, P.; Li, X.; Xia, C.; Li, F. (Chem. Commun., 2016)

(untitled) - Mandal, S.; Bera, T.; Dubey, G.; Saha, J.; Laha, J. K. (ACS Catal., 2018)

(untitled) - Sutherland, D. R.; Veguillas, M.; Oates, C. L.; Lee, A.-L. (Org. Lett., 2018)

(untitled) - Liu, Q.; Wang, Q.; Xie, G.; Fang, Z.; Ding, S.; Wang, X. (Eur. J. Org. Chem., 2020)

(untitled) - Liu, Q.; Xie, G.; Wang, Q.; Mo, Z.; Li, C.; Ding, S.; Wang, X. (Tetrahedron, 2019)

(untitled) - Lu, D.; Wan, Y.; Kong, L.; Zhu, G. (Org. Lett., 2017)

(untitled) - Hanchate, V.; Devarajappa, R.; Prabhu, K. R. (Org. Lett., 2020)

(untitled) - Janesko, B. G.; Fisher, H. C.; Bridle, M. J.; Montchamp, J.-L. (J. Org. Chem., 2015)

(untitled) - Zhao, J.; Li, P.; Xu, Y.; Shi, Y.; Li, F. (Org. Lett., 2019)

(untitled) - Li, P.; Zhao, J.; Shi, L.; Wang, J.; Shi, X.; Li, F. (Nat. Commun., 2018)

(untitled) - Li, P.; Zhao, J.; Xia, C.; Li, F. (Org. Chem. Front., 2015)

(untitled) - Zhao, J.; Li, P.; Xia, C.; Li, F. (Chem. Commun., 2014)

(untitled) - Li, P.; Zhao, J.; Xia, C.; Li, F. (Org. Lett., 2014)

(untitled) - Zhang, H.-Y.; Mao, L.-L.; Yang, B.; Yang, S.-D. (Chem. Commun., 2015)

(untitled) - Gao, M.; Li, Y.; Xie, L.; Chauvin, R.; Cui, X. (Chem. Commun., 2016)

(untitled) - Zhu, L.; Yu, H.; Guo, Q.; Chen, Q.; Xu, Z.; Wang, R. (Org. Lett., 2015)

(untitled) - Yang, W.-C.; Dai, P.; Luo, K.; Ji, Y.-G.; Wu, L. (Adv. Synth. Catal., 2017)

(untitled) - Che, C.; Huang, Q.; Zheng, H.; Zhu, G. (Chem. Sci., 2016)